Die befreiten Geiseln Kaiser Tewodros’ II. Aus dem Photoalbum der Royal Engineers 1867/68 - Gräber, Gerd (Aethiopica, 1999)
The famous Robert Lebeck Collection of historical photographs, which has been preserved in the Agfa Foto-Historama in the Wallraf-Richartz Museum/ Museum Ludwig, Cologne, since 1994, contains an album entitled “Views of the Abyssinian Campaign – presented by Lord Napier of Magdala”. With its 78 albumen prints, taken by the photographers of the 10th Company, Royal Engineers–Great Britain, it seems to be a unique but scarcely known source for Ethiopian studies. To our present knowledge, they are the earliest photographic documents related to Ethiopia. In this article the author gives a detailed analysis of three prints (Nr.: 58, 59, 60) showing the released captives on whose behalf the “crusade” of the Magdala-expedition was undertaken in 1867/68, and makes an attempt to identify the persons on the photos. Many of these persons left an indelible impact on the 19th century Ethiopian history through their roles as counsellors, missionaries, scientists or artisans.